Virtual Reality: As a Transformation to Rebuild the Tourism Sector in Badung District - Putri Kirana, Ni Nyoman; Putri Wulandari, Ni Made; Sri Kayika Putri, I Gusti Ayu (International Journal of Educational Technology and Artificial Intelligence, 2023)
Badung Regency has the highest local revenue (PAD) in the province of Bali. In addition, Badung Regency has a lot of exciting tourism potential, but unfortunately, this tourism potential is still not well known by the public. As a result of the COVID-19 pandemic, the tourism sector in Badung Regency has experienced a decline due to restrictions on community activities not being allowed to visit a tourist spot directly. Therefore, a solution is needed to overcome this problem, one of which is utilizing information technology currently developing in society, such as Virtual Reality. Virtual Reality can be the key to promoting tourism potential in Badung Regency so that the tourism sector can revive. Through Virtual Reality, users can directly interact and get information about the tours to be visited digitally. This virtual reality application is built on a website so everyone can easily access it. The design of this application uses the MDLC (Multimedia Development Life Cycle) method, which consists of 6 stages: Concept, Design, Material Collecting, Assembly, Testing, and Distribution, after designing a Virtual Reality application using 3sixty software. Furthermore, this Virtual Reality was evaluated through a questionnaire that was tested by 15 SMA Negeri (Public Senior High School) 2 Abiansemal students so that the test results can conclude that Virtual Reality can potentially improve the tourism sector in Badung Regency. Therefore, Virtual Reality can help revive Regional Original Revenue (PAD) in Badung Regency through the tourism sector.